Preservice Student-Teachers’ Perceptions of Themselves as Teachers- Experience from Teaching Practicum - Fotopoulou, Vasiliki (European Journal of Multidisciplinary Studies, 2017)
The importance and significance of the role of pre-service teachers’ education in building up their identity formation is well-recognized. This work investigates one dimension of this complex formation: how pre-service teachers perceive themselves as teachers in a pre-service teacher education compulsory course of teaching practice in Greece. An experience report from a teaching practicum is presented based on a qualitative analysis of anonymous questionnaires (N=144). Our analysis reveals that student-teachers are engaged in a process of transformation which encompasses from the academic preparation to the teaching reality. We identify three interconnected stages in this transformation process: i) first contact (e.g., choice and field of their studies, relation between theory and practice), ii) familiarization (e.g., get in touch with teaching activity, with the space and the operation of kindergarten, collaboration with teachers), and iii) function (e.g., interaction with pupils, acquiring experience, acting as teachers). According to the data analysis, preservice teachers tend to attribute greater importance to specific elements of each stage. More specifically, the choice and field of their studies as well as the teaching activity (planning, implementation and feedback) were underlined as very important elements in the second and third stage respectively, while a great number of preservice students highlighted the interaction with students in the classroom as well as their act and operation as teachers in the third stage. Summing up, our findings indicate that pre-service teachers perceive themselves as teachers through four-correlated to each other in a bidirectional manner- issues: the academic framework, the teaching activity, themselves acting as teachers, and the students. Furthermore, the aforementioned four issues point out that pre-service teachers’ perceptions are not stable but are subjected to a transformative process that take place during their teaching practice. Accordingly, the findings of this study could provide a conceptual framework that incorporates pre-service teachers’ perceptions and examine teachers’ identity formation from this specific perspective of pre-service studies.